Intellectual and spiritual expression of non-literate peoples : proceedings of the XVII UISPP World Congress (1-7 September, Burgos, Spain). - Anati, Emmanuel (Archaeopress archaeology., 2016)
Proceedings of the session 'Intellectual and Spiritual Expression of Non-literate Peoples', part of the XVII World UISPP Congress, held in Burgos, 2014. The session brought together experts from various disciplines to share experience and scientific approaches for a better understanding of human creativity and behaviour in prehistory.